Implementation of The Five R Concept Evidence from Warehouse Of Bank Rakyat Indonesia Yumaga Unit Serang City - Yanto Heryanto; Siti Sofiyah (PT. EQUATOR SINAR AKADEMIA, 2023)
The problem discussed is how to implement the 5R concept (Concise, Neat, Clean, Treat, Diligent) in the PT. Bank Rakyat Indonesia Yumaga. The data collection method used is the observation method (observation). The purpose of making this final report is to find out how the implementation of the 5R concept has been carried out in an effort to avoid document loss and the efficiency of time in searching for documents that are not too long. The result of this observation indicate that the condition of the warehouse is not neat and the many piles of cardboard containing documents that are not of the same type cover the warehouse aisle, this can be seen from the placement of objects that are not in place. Based on the observations that have been made, it can be concluced that the 5R concept in the PT. Bank Rakyat Indonesia can be implemented through: 5R prepation stages, introduction of 5r, implementation of 5R. There were several obstacles found, such as cramped warehouse conditions, lack of employee awareness to carry out the 5R concept, and employee turnover chaing places of work.